The Effect of Perceived Ease of Use and Perceived Usefulness on Intention to Use Digital Hajj Registration with Trust as a Moderating Variable (A Study of Bank Muamalat Malang Branch Customers) - Ilma Ma'rifatus Zuhro Asyhari; Rini Safitri (FAKULTAS EKONOMI DAN BISNIS ISLAM, 2026)
Abstract Purpose: This study aims to examine the effect of Perceived Ease of Use and Perceived Usefulness on the Intention to Use digital Hajj registration services, as well as to analyze the role of Trust as a moderating variable. Design/methodology/approach: This research employs a quantitative approach using a survey method. Data were collected from 200 respondents who are customers of Bank Muamalat Malang Branch through questionnaires. The data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with the help of SPSS version 26). Research Findings: The results show that Perceived Ease of Use has a positive and significant effect on Intention to Use, while Perceived Usefulness does not have a significant effect. Furthermore, Trust does not moderate the relationship between Perceived Ease of Use and Intention to Use, but it significantly strengthens the relationship between Perceived Usefulness and Intention to Use. Simultaneously, all variables have a significant effect on user intention. Contribution/Originality/Novelty: This study contributes to the development of the Technology Acceptance Model (TAM) by incorporating Trust as a moderating variable in the context of Islamic digital banking services, particularly digital Hajj registration. It also provides practical insights for financial institutions to enhance system usability and build user trust to increase digital service adoption. Keywords: Perceived Ease of Use, Perceived Usefulness, Trust, Intention to Use, Digital Banking .